Pengaruh Kepemimpinan Dan Pelatihan Kerja Terhadap Kinerja Karyawan Pada PT Pos Indonesia (Persero) Cabang Ciputat Kota Tangerang Selatan - Nurul Azizah Thiffal; Noryani Noryani (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
The purpose of this study is to determine the effect of leadership and job training on employee performance at PT Pos Indonesia (Persero) Ciputat Branch, South Tangerang City. This research uses a quantitative method with an associative approach. The sampling technique applied is saturated sampling, involving 110 respondents. Data analysis techniques include validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results indicate that leadership has a significant effect on employee performance with a coefficient of determination of 23.4%, and the hypothesis test shows that t value > t table (5.742 > 1.980). Job training also has a significant effect on employee performance with a coefficient of determination of 32.4%, and the hypothesis test result shows t value > t table (7.202 > 1.980). Simultaneously, leadership and job training have a significant effect on employee performance with the regression equation Y = 13.877 + 0.209X1 + 0.451X2. The coefficient of determination is 36.0%, while the remaining 64,0% is influenced by other factors. The hypothesis test shows that F value > F table (30.042 > 3.08).